Subjectivity and Subordination in The Hour of the Star, by Clarice Lispector - Baltodano Román, Gabriel (2019)
An analysis is presented of the novel A hora da estrela (The Hour of the Star; 1977), by the Brazilian writer Clarice Lispector. This novel has been the object of study in contemporary feminist circles, since it offers a clear literary representation regarding the processes of the conformation of subjectivities marked by violence of gender, race and social class. This study aims to contribute to a better knowledge of this literary text within our cultural environment, thus focusing on the examination of one specific issue: the principles and procedures involved in the process of shaping the female character.